The Imaginary Divan. Philosophy of representation (Devenires, 2007)
The paper talks about how the faculty of representation is not a theatrical element only, but also cultural, in a way of how this faculty is applied to replace the real order to an imaginary one, the things for the ideas, the impulses for the principles, the matter for the form. It also explores the similarities and differences between the theater and the social sphere created in the modern days, where the people has to play roles to maintain themselves in a society, expressing gestures and moves that does not require any dramatic skills but emanates from the conditions created by humanity.
Keywords: Representation; theatre; imaginary